Recurrent retroperitoneal cystic lymphangioma - Ozdemir, H; Kocakoc, E; Bozgeyik, Z; Cobanoglu, B (Yonsei Univ College Medicine, 2005)
Retroperitoneal cystic lymphangioma is a rare congenital malformation. The majority of lymphangiomas are present at birth and nearly all present before the age of two years. We report a case of giant cystic retroperitoneal lymphangioma in a patient who first presented with symptoms at the age of 7, underwent surgery, and who then suffered a recurrent mass 11 years later.
Keywords: lymphangioma; retroperitoneal; ultrasonography; computed tomography; magnetic resonance imaging